The impact of COVID-19 on the Spanish tourism sector. Issue 3 (May 2022) - Gil-Alana, Luis Alberiko; Poza, Carlos
We examine in this note the impact of COVID-19 on the Spanish tourism sector by using a strong dependence model. Daily data from five equity markets are used and we find that the coronavirus crisis has increased the persistence in the data, moving in some of the series from a mean reverting process to a non-mean reverting one. Thus, shocks that were expected to be transitory have become permanent, implying the need of strong policy measures to come the series back to their long-term projections.